2020
DOI: 10.1007/s13762-020-02667-3
|View full text |Cite
|
Sign up to set email alerts
|

Metals concentrations in road dust from high traffic and low traffic area: a size dependent comparison

Abstract: Metals in road dust are increasingly investigated. The fine size fractions are of particular importance because of their higher mobility and the increased concentrations of pollutants. In this study, two average road dust samples from areas with highand low-traffic density were investigated. Prior to chemical analysis, a combined sieving and air classification procedure was applied where the road dust samples were split into seven size fractions. The metal concentrations in the road dust from the low-traffic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Our results also showed that cell viability in the presence of particles collected from HT areas was significantly higher than in particles collected from LT areas. This result seems logical because similar to our findings, earlier studies reported a higher concentration of HMs in the HT area compared to LT one [ 44 , 45 ]. In terms of cytotoxicity, the effect of exposure to DPs on cell viability of cancer cells such as A549 and AGS was higher than that of normal cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also showed that cell viability in the presence of particles collected from HT areas was significantly higher than in particles collected from LT areas. This result seems logical because similar to our findings, earlier studies reported a higher concentration of HMs in the HT area compared to LT one [ 44 , 45 ]. In terms of cytotoxicity, the effect of exposure to DPs on cell viability of cancer cells such as A549 and AGS was higher than that of normal cells.…”
Section: Discussionsupporting
confidence: 92%
“…State Highway-49, NH 66 and NH 45A linking to Puducherry (India). Miazgowicz et al (2020) also documented that, in the soil samples from the high-traffic area collected from different parts of Krakow, Poland, the respective concentrations of Cu, Fe, Mn and Zn were 1.2, 3.0, 3.2 and 5.4 times more than low-traffic area.…”
Section: Introductionmentioning
confidence: 83%
“…Calculations of EF values showed that Sb, Zn, Mo, Cu and Pb were the main pollutants of Surgut's road dust (See Table 3). The main source of Sb in road dust is brake wear [79]. Antimony pentasulfide is used as a pigment in the production of car tires [80].…”
Section: Source Identificationmentioning
confidence: 99%